2018
DOI: 10.3390/jof4030106
|View full text |Cite
|
Sign up to set email alerts
|

Sporothrix schenckii Cell Wall Proteins-Stimulated BMDCs Are Able to Induce a Th1-Prone Cytokine Profile In Vitro

Abstract: Sporotrichosis is a subcutaneous mycosis affecting humans and other animals. The disease can be acquired by accidental inoculation of the fungus through the skin or through the respiratory system. Sporotrichosis can also be transmitted through bites or scratches by infected cats and more rarely by other animals (zoonotic transmission). Conventional antifungal therapy is especially inefficient in immunocompromised patients, who tend to develop the most severe forms of the disease, thus prompting the search for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…And, treatment with Amphotericin B (AmB) enhances the in vitro production of Il1β and Tnfα in peritoneal macrophages. 33 S. schenckii is able to promote BMDC maturation and increase Tnfα production, 34 and it seems that Tnfα contributes to the host defence against sporotrichosis infection. It has been reported that mast cells can be directly activated by inducing de novo synthesis of the inflammatory mediators, Tnfα and Il-6.…”
Section: Discussionmentioning
confidence: 99%
“…And, treatment with Amphotericin B (AmB) enhances the in vitro production of Il1β and Tnfα in peritoneal macrophages. 33 S. schenckii is able to promote BMDC maturation and increase Tnfα production, 34 and it seems that Tnfα contributes to the host defence against sporotrichosis infection. It has been reported that mast cells can be directly activated by inducing de novo synthesis of the inflammatory mediators, Tnfα and Il-6.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that Th1 response plays a decisive role in the defense against S. schenckii infection [32,33,34,35]. In this sense, activation of Th1 lymphocytes is becoming an interesting immunomodulatory strategy against sporotrichosis.…”
Section: Discussionmentioning
confidence: 99%
“…AFCo3 stimulated a strong Th1- and Th17 response associated with the antifungal effect of AmB, which significantly improved the fungal clearance [37]. Regarding vaccination, studies suggest that Th1 response is associated with anti-sporothrix vaccine protection [20,21,22,38,39] and the activation of dendritic cells by fungal wall proteins seems to be important in theTh1 bias [34]. However, the role of Th17 response to prevent sporotrichosis is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The protein Gp70 has been one of the candidates to develop an anti- Sporothrix vaccine [17,18,19,20,21,22,23], but other alternatives, such as formulations using cell wall glycoproteins, have also provided promising results, which are underscored by the development of protective responses upon immunization with these preparations [24]. Here, Quinello et al, provide new information on the use of dendritic cells as alternatives to deliver fungal epitopes to stimulate a protective anti- Sporothrix response [25]. Mouse bone-marrow-derived dendritic cells were stimulated with S. schenckii cell wall proteins and then cocultured with splenocytes.…”
mentioning
confidence: 99%
“…Mouse bone-marrow-derived dendritic cells were stimulated with S. schenckii cell wall proteins and then cocultured with splenocytes. As a result, the activated dendritic cells stimulated a cytokine profile suitable for the activation of the Th1 cell population, suggesting the cell wall preparation could lead to the establishment of a protective antifungal response [25]. Since the study was conducted in an in vitro setting, this observation still needs to be confirmed in the animal model of sporotrichosis.…”
mentioning
confidence: 99%